A New Estimator of Search Duration and Its Application to the Marriage Market - Pavel Jelnov (Institute of Labor Economics (IZA), 2018)
It is well known that female age at first marriage positively correlates with male income inequality. The common interpretation of this fact is that marital search takes longer when the pool of potential mates is more unequal. This paper challenges that interpretation with a novel econometric method. I utilize the fact that the female age at first marriage was shown to be a sum of a skewed term, possibly related to search, and a normally distributed residual. I estimate search duration as the expected skewed term. I find that in the American data this term does not positively correlate with male income inequality and female education.
Keywords: J12; D83; 330; marital search; marriage age; inequality; female education